IMPLIKASI KRONOLOGI BANGSA ISRAEL KELUAR DARI MESIR DALAM KITAB KELUARAN BAGI ORANG PERCAYA - Sabda Budiman; Krido Siswanto (STTII PURWOKERTO, 2021)
The most interesting event in the Old Testament is the history of the exodus of the Israelites from the land of Egypt recorded in the Book of Exodus. how did the history of the Israelites come out of the land of Egypt and what is the relevance of the chronology of the Israelites out of Egypt in the Book of Exodus for today's believers? The purpose of this article is to explain the history of the Israelites coming out of the land of Egypt and explain the relevance of the chronology of the Israelites coming out of Egypt in the Book of Exodus for today's believers. The method used in this scientific work is qualitative research method with descriptive approach. Any data which in this case is in the form of literature and interpretations of the Bible collected and analyzed, becomes the key to what is analyzed and examined. The result of this study is that the chronology of the Israelites coming out of Egypt has the implication that God commits sin and gives space for man to repent, Jesus becomes the Passover lamb for today's believers, and God always leads believers in His way and plan.